INTRODUCING OPTICAL MICROSCOPY METHODOLOGY DISPLAYING EMITTED ELECTROMAGNETIC ENERGY OF PRE-CANCEROUS SKIN SQUAMOUS CELL CARCINOMA - Embi, Abraham A. (International Journal of Research -GRANTHAALAYAH, 2023)
Ever since the development in 2015 (Embi et al. (2015), Scherlag et al. (2015)) and published in 2016 Scherlag et al. (2016) of a tabletop microscopy methodology aimed to record plant and animal tissue energy in the form of electromagnetic radiation (EMR), this author and others have had the opportunity to explore and publish in the less traveled road of Biophysics. This was mainly done by using an easily accessible human miniorgan, namely a hair follicle Schneider et al. (2009).